Highly active and stable Au@CuxO core–shell nanoparticles supported on alumina for carbon monoxide oxidation at low temperature. Issue 79 (8th August 2016) - Zhang, Weining; Zhao, Qingguo; Wang, Xiaohong; Yan, Xiaoxia; Han, Sheng; Zeng, Zhigang
Abstract : Au@Cu x O core–shell nanoparticles and Au@Cu x O/Al2 O3 used for CO oxidation at low temperature are prepared. CO conversion on Au@Cu x O/Al2 O3 can reach to 38% at room temperature and the catalytic activity remains unchanged after 108 hours reaction. Abstract : Au@Cu x O ( x = 1 or 2) core–shell heterostructure nanoparticles (NPs) are synthesized by a facile aqueous solution approach. γ-Alumina support Au@Cu x O (Au@Cu x O/γ-Al2 O3 ) catalysts used for CO oxidation at low temperature are prepared by dispersing the core–shell NPs on the surface of γ-alumina. It proves that the formation of the core–shell structure has led to the interaction between Au and Cu x O and the co-existence of Au δ + and Au 0, which accounts for the improvement in catalytic activity. It can even catalyze CO oxidation at room temperature and the conversion of CO can reach to 38%. In the same case, Au/γ-Al2 O3 does not have any catalytic activity. In particular, the embedding of Au NPs into Cu x O shells has also improved the catalytic stability of Au based catalysts remarkably, which remains unchanged after 108 hours of reaction. To the best of our knowledge, Au@Cu x O/γ-Al2 O3 is really one of the most stable catalysts with adequate activity at room temperature.